Efficacy of intralesional meglumine antimoniate in the treatment of canine tegumentary leishmaniasis: A Randomized controlled trial - Lago, Jamile; Fraga, Deborah; Guimarães, Luiz Henrique; Lago, Tainã; Santos, Yuri; Lago, Ednaldo; Werneck, Guilherme L.; Bacellar, Olívia; Carvalho, Edgar M. (PLOS Neglected Tropical Diseases, 2023)
Dogs living in areas of Leishmania (Viannia) braziliensis transmission may present canine tegumentary leishmaniasis (CTL) characterized by cutaneous or muzzle ulcers as well as asymptomatic L. braziliensis infection. It is not clear if dogs participate in the transmission chain of L. braziliensis to humans. However, dogs may remain with chronic ulcers for a long time, and as there are no public policies about CTL, these animals die or are sacrificed. Here we compare the efficacy of intralesional meglumine antimoniate with intralesional 0.9% NaCl solution in CTL treatment. This randomized control study included 32 dogs with cutaneous or muzzle lesions who had L. braziliensis DNA detected by PCR in tissue biopsied. Group one received 5ml of intralesional Glucantime, and group two received 5ml 0.9% NaCl solution, both applied in the four cardinal points on days 0, 15, and 30. Cure was defined as complete healing of the ulcers in the absence of raised borders on day 90. There was no difference in animals’ demographic and clinical features in the two groups (p >.05). While at the endpoint, the cure rate was 87.5% in the group test, and in those who received 0.9 NaCl the cure rate was only 12.5%. As important as the high cure rate, the healing time was faster in dogs treated with antimony than in those treated with saline (p < .001). Intralesional meglumine antimoniate is effective in the treatment of dogs with L. braziliensis infection and accelerates the healing time of CTL.